2006
DOI: 10.1194/jlr.m600182-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Agrin elicits membrane lipid condensation at sites of acetylcholine receptor clusters in C2C12 myotubes

Abstract: The formation of the neuromuscular junction is characterized by the progressive accumulation of nicotinic acetylcholine receptors (AChRs) in the postsynaptic membrane facing the nerve terminal, induced predominantly through the agrin/muscle-specific kinase (MuSK) signaling cascade. However, the cellular mechanisms linking MuSK activation to AChR clustering are still poorly understood. Here, we investigate whether lipid rafts are involved in agrinelicited AChR clustering in a mouse C2C12 cell line. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 71 publications
12
50
0
Order By: Relevance
“…Cartaud et al suggested that raft lipid domains were involved in the sorting and subsequent delivery of AChR and rapsyn to the plasma membrane ( 16 ) and that AChR was constitutively associated with raft lipid domains together with syntrophin, rapsyn, and other postsynaptic components, independently of agrin stimulation ( 17 ). Agrin activation of MuSK was necessary, however, for inducing the coalescence of rafts and for AChR clustering.…”
Section: Preparation Of Achr Membranes Crude Achr-membranesmentioning
confidence: 99%
“…Cartaud et al suggested that raft lipid domains were involved in the sorting and subsequent delivery of AChR and rapsyn to the plasma membrane ( 16 ) and that AChR was constitutively associated with raft lipid domains together with syntrophin, rapsyn, and other postsynaptic components, independently of agrin stimulation ( 17 ). Agrin activation of MuSK was necessary, however, for inducing the coalescence of rafts and for AChR clustering.…”
Section: Preparation Of Achr Membranes Crude Achr-membranesmentioning
confidence: 99%
“…Rapsyn stability is increased at the synapse by the chaperone Hsp90b, and rapsyn interacts with and inhibits calpain, and thus antagonizes the AChR cluster-dispersing effect of ACh. Agrin signaling is regulated by Musk endocytosis, the E3 ubiquitin ligase Pdzrn3, lipid microdomains (Kishi et al, 2005;Stetzkowski-Marden et al, 2006;Willmann et al, 2006;Zhu et al, 2006) and intracellular calcium (Megeath and Fallon 1998). Many pathways illustrated here have been identified in cultured muscle and non-muscle cells, and their role in vivo remains to be studied.…”
Section: Lrp4 As An Agrin Co-receptormentioning
confidence: 99%
“…However, several receptors and transmembrane proteins of the postsynaptic density (PSD) purify with detergent-resistant membrane (DRM) fractions, indicating a possible association with lipid rafts. Examples of this are acetylcholine receptors (Stetzkowski-Marden et al, 2006; references in Allen et al, 2007), K ϩ channels (Wong and Schlichter, 2004), and glutamatergic receptors (Hering et al, 2003). Extrinsic membrane scaffolding proteins associated with excitatory synapses (GRIP, PSD-95) (Hering et al, 2003) are also purified in DRM fractions.…”
Section: Introductionmentioning
confidence: 99%